Analisis Ergonomi Keluhan Musculoskeletal Disorders pada Pekerja Tenun Ikat di Desa Ternate, Kabupaten Alor - Sartono S. Rika; Luh Putu Ruliati; Deviarbi Sakke Tira (Universitas Nusa Cendana, 2022)
Complaints of musculoskeletal disorders (MSDs) affect the parts of the body involved in carrying out a job. The complaints of MSDs that often arise in weaving workers are often related to the pain experienced in the back and neck, wrists, elbows and feet. If the muscles receive static loads repeatedly for a long time, it can cause damage to muscles, nerves, tendons, joints, cartilages and intervertebral discs. The purpose of this study was to analyze ergonomics with MSDs in weaving workers in Ternate Village, Alor District. This research was a quantitative analytic study with a cross-sectional design. The population of this study were all weavers in Ternate Village with a total of 45 people, all of whom were women. The sample consisted of 45 people selected by a total sampling technique. The results showed that tenure, work posture, workload, work time and lighting were related with MSDs in weaving workers in Ternate Village, Alor district with ρ-value < α (0.05). There was no relationship between temperature and complaints of musculoskeletal disorders with a ρ-value > α (0.05). Weavers need to improve work posture, and take the rest time to reduce workload and worktime.